2017
DOI: 10.1021/acs.jpcb.7b09619
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Endocytosis of Nanoparticles: Roles of Shapes, Orientations, and Rotations of Nanoparticles

Abstract: A complete understanding of the interactions between nanoparticles (NPs) and the cell membrane is essential for the potential biomedical applications of NPs. The rotation of the NP during the cellular wrapping process is of great biological significance and has been widely observed in experiments and simulations. However, the underlying mechanisms of the rotation and their potential influences on the wrapping behavior are far from being fully understood. Here, by coupling the rotation of the NP with the diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 59 publications
5
29
0
Order By: Relevance
“…Furthermore, the shape can affect nanosystem phagocytosis by macrophages, i.e., the nanoparticle-cell contact point determines whether macrophages initiate internalization or are simply spread on nanosystems in which the Ω angle is a crucial criterion ( Figure 6 d). The spherical shape is then an ideal shape to induce phagocytosis of the nanosystem since it has Ω angle of less than 45° [ 268 , 270 ].…”
Section: Pharmacokinetics Biodistribution and Nanotoxicologymentioning
confidence: 99%
“…Furthermore, the shape can affect nanosystem phagocytosis by macrophages, i.e., the nanoparticle-cell contact point determines whether macrophages initiate internalization or are simply spread on nanosystems in which the Ω angle is a crucial criterion ( Figure 6 d). The spherical shape is then an ideal shape to induce phagocytosis of the nanosystem since it has Ω angle of less than 45° [ 268 , 270 ].…”
Section: Pharmacokinetics Biodistribution and Nanotoxicologymentioning
confidence: 99%
“…15 It has been shown that the energy-dependent endocytosis pathways, rather than passive diffusion, are the main mechanisms that cell lines use for nanoparticle uptake. 16,17 Specically, receptormediated endocytosis (RME) is known to be one of the main uptake pathways for AuNPs. For RME, the biomolecules attached to the AuNP surface bind to the extracellular surface of the plasma membrane receptor and membrane fusion is induced.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of membrane curvature, particle shape and orientation, and interactions between NPs on the wrapping process are not considered. Fortunately, the effects of these factors have been discussed in the existing literature [ 27 , 28 , 29 , 30 , 31 ]. Remarkably, Tang et al recently formulated a model to theoretically investigate the effects of the particle shape and orientation, and interactions between NPs, on wrapping process.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, Tang et al recently formulated a model to theoretically investigate the effects of the particle shape and orientation, and interactions between NPs, on wrapping process. Their results revealed the roles of the shape, rotation, and initial orientation of the NP, and interactions between NPs, on receptor-mediated endocytosis, and provide good guidelines for the design of NP-based drug delivery systems [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%